The perception of Standard Chartered Bank Malaysia Berhad's clerk on the motivational impact of the sales incentive scheme on their effort, participation, teamwork, emotion and commitment - Taiban, Hussain (1999)
This study examines the perception of the clerk on the motivational impact of the Sales Incentive Scheme. Specifically it intend (i) to identify the clerk's perception regarding the motivational impact of the Sales Incentive Scheme on their effort, participation, teamwork, emotion and commitment, (ii) to examine the inter-relationship of these motivational impact areas base on the clerical perception, and finally (iii) to rank the identified impact areas. The respondents for this study comprised of sixty-one clerical staff from all the six branches of the Standard Chartered Bank Malaysia Berhad, Consumer Banking Division in the Sarawak Region. Questionnaires were used in collecting the data for the study. Five impact areas were identified for this study, which are effort, staff participation, teamwork, emotion and commitment. Descriptive statistics (frequency and mean) and inferential statistics (correlation and Anova) were used to analyse the data. - The major findings of this study are: (i) that the Sales Incentive Scheme has motivate the clerical to put an effort to perform sales, but (ii) it does not push them to participate; (iii) did not create a healthy working relationship,{iv) was not perceived as a source of happiness; and (v) has not been able to generate the level of commitment that the bank want. There is a negative inter-relationship between all the impact areas except for the relationship between teamwork with participation, and emotion with effort. Effort is perceived as the most important area in term of ranking, followed by participation, teamwork, commitment and emotion.